Karakteristik Batuan Tuff Pada Daerah Mootilango Kabupaten Gorontalo Utara Provinsi Gorontalo - Muh Hasym As'ari; Ahmad Zainuri; Muhammad Kasim (Geosfera: Jurnal Penelitian Geografi, 2025)
The study area is located in Mootilango Village Anggrek Sub-district, North Gorontalo Regency, Gorontalo Province. Geographically, the study area is located at coordinates 0° 46' 0" - 0° 46' 45” LU and 122° 48' 0” - 122° 48' 45" BT with an area of about 3.7 km². The purpose of this study was to determine the characteristics of tuff rocks through petrological, petrographic and geochemical analysis in the laboratory. The results of petrological identification show that the rock types are coarse tuff, fine tuff and pyroclastic breccia. The results of petrographic analysis show that the tuff in this area belongs to Vitric tuff according to the classification of Schmid (1981). The results of geochemical analysis show that the tuff in the study area belongs to the basalt-andesite type transition rock group according to the classification of Le Bas et al. (1986). Two classification approaches were used in the analysis to determine the magma series of the rock, namely according to Irvine and Baragar (1971), which shows that the rock belongs to the tholeiitic magma series.